Corruption in Russia - Günther G. Schulze; Bambang Suharnoko Sjahrir; Nikita Zakharov (University of Freiburg, Department of International Economic Policy (iep), 2013)
Analyzing law enforcement data on corruption incidents for a panel of 79 Russian regions for the period 2004-2007, we find that the relative salaries of bureaucrats determine corruption levels: Corruption declines as relative salaries rise up to a turning point, beyond which corruption rises again. Other important determinants are the strength of law enforcement, available rents through government budgets and natural resources, education levels, unemployment rates, and income inequality.
Keywords: K42; H10; P26; 330; Corruption; Russia; bureaucracy; law enforcement